2003
DOI: 10.1063/1.1619373
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the HO2+NO reaction: Prediction of the total rate constant and product branching ratios for the forward and reverse processes

Abstract: The mechanisms for HO2+NO and its reverse reactions have been investigated by ab initio molecular orbital and transition-state theory calculations. The species involved have been optimized at the B3LYP/6-311+G(3df,2p) level and their energies refined by single-point calculations with the highest scheme of the modified Gaussian-2 method. Ab initio results show that formation of HO+NO2 from HO2+NO by the direct fragmentation of the peroxynitrous acid, HOONO intermediate, is predominant; the alternative path occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 80 publications
4
24
0
Order By: Relevance
“…Atkinson et al [52] suggested that the production of HOONO in the gas phase cannot be ignored, and Nizkorodov and Wennberg [53] made spectroscopic observations of gas-phase HOONO. Both HNO 3 and HOONO are likely produced in the gas phase by reactions of NO 2 with OH, and NO with HO 2 as discussed above [54][55][56]. When OH reacts with the O atom in ONO (the same as NO 2 but representing the molecular structure), the linear molecule HOONO is produced.…”
Section: Rnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atkinson et al [52] suggested that the production of HOONO in the gas phase cannot be ignored, and Nizkorodov and Wennberg [53] made spectroscopic observations of gas-phase HOONO. Both HNO 3 and HOONO are likely produced in the gas phase by reactions of NO 2 with OH, and NO with HO 2 as discussed above [54][55][56]. When OH reacts with the O atom in ONO (the same as NO 2 but representing the molecular structure), the linear molecule HOONO is produced.…”
Section: Rnsmentioning
confidence: 99%
“…In experiments [53,54], HOONO was determined by a ratio of HOONO/HNO 3 , which ranges from 5% to 30%. Rate coefficients for the reaction of OH and NO 2 , 1.57 × 10 −11 cm −3 s −1 ; and for the reaction of HO 2 and NO, 2.31 × 10 −13 cm −3 s −1 [55,56], produce a ratio of HOONO/HNO 3 of ≈40% in the gas phase. The production of HOONO and HNO 3 consumes a small portion of the NO and NO 2 .…”
Section: Rnsmentioning
confidence: 99%
“…In addition, the protonated form HOONO However, it was five years later when it was realized that this has been found to be important in atmospheric chemistry [8]. was a peroxide isomer and not the more stable D3h isomer with a These applications have resulted in a number of theoretical central N [2].…”
mentioning
confidence: 99%
“…Given the importance of the HO 2 + NO reaction in the atmosphere, several publications have been investigated, and as a result, the kinetics of this reaction has been studied experimentally [8][9][10][11][12][13] and theoretically [14][15][16][17][18][19][20][21] for a range of temperature. Meanwhile, as the significant enhancement [22][23][24] of H 2 O in the HO self-reaction is explained by the formation of the H 2 OÁÁÁHO 2 complex, a similar mechanism may occur in other HO 2 radical reactions, particularly in Equation (2).…”
Section: Introductionmentioning
confidence: 99%
“…HNO 3 ) and indirect [47,54] The B3LYP functional [55,56] has proven to be a reliable DFT method for describing the geometries, zero-point energies (ZPEs), and frequencies for the HO 2 + NO reaction in previous studies. [7,21] As a result, the geometries of all the stationary points, including reactants, complexes, transition states (TSs), and products for the HO 2 + NO reaction without and with medium X (X = H 2 O, (H 2 O) 2 , NH 3 , and H 3 NÁÁÁH 2 O), are optimized at the B3LYP/6-311 + G(2df,2p) level, carried out using the Gaussian 09 program package. [57] Harmonic vibrational frequencies have been calculated at the same level to determine the minimum energy equilibrium structures, which possess all real frequencies, while the TS has a single imaginary frequency.…”
Section: Introductionmentioning
confidence: 99%